From nostalgia to trend: a systematic review of vinyl record consumption and perspectives for future research (Revista Brasileira Multidisciplinar, 2024)
In recent years, the consumption of vinyl records has experienced steady growth. Vinyl records provide a unique and authentic consumption experience through their physical characteristics and distinctive sound quality. This study aims to analyze the research field concerning the consumption of vinyl records and present suggestions for future research. A systematic literature review was conducted using the Web of Science and Scopus databases, examining 29 articles on the topic. The results revealed a limited number of studies, leading to a lack of prominent authors, institutions, and journals to serve as references. Several thematic clusters were identified, along with four groups of suggestions for future research: consumption and market; consumption of cultures and groups; nostalgia; and feelings and emotions. These themes indicate areas and questions to be explored and debated in subsequent studies in the field of vinyl record consumption. It is concluded that, despite the growing demand for vinyl records, the research field on their consumption remains limited and does not keep pace with the (re)expansion of the market. Further studies are needed to better understand consumer motivations, consumption patterns, and the impact of this phenomenon on the music market.
Keywords: Vinyl record; Consumption; Marketing